PHONOLOGICAL COMPETENCE OR COMPETENT PHONOLOGY? - Moubarik, Mustapha (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In this paper we discuss whether the learner of English should aim at acquiring native-like pronunciation, or instead, intelligible pronunciation, i.e. competent phonology, is sufficient for his/her needs. It offers a brief review of research in language acquisition in general and phonological competence in particular. We draw on our lengthy experience as a learner and teacher of foreign languages at both secondary and tertiary levels. We also discuss pedagogical implications, insisting on the pressing need to enhance home-made materials designed and produced by non-native speakers, because these are better placed to know the needs of their learners on the one hand, and the goals of language learning in their own environments on the other.